A FRAMEWORK FOR INTEGRATING ESG CRITERIA INTO STRATEGIC HUMAN RESOURCE PLANNING - M Saiful Rizal; Handoko Teguh (Penelitian dan Pengembangan Ilmu, 2025)
The global shift from shareholder primacy to stakeholder capitalism has put criteriaEnvironmental, Social, and Governance(ESG) as the gold standard for corporate success. However, there is a significant gap between high-level ESG commitments and tactical implementation in Human Resource Management (HRM). This study develops a conceptual framework for integrating ESG criteria into strategic HR planning through a systematic narrative review of the literature from 2016–2026. The study reveals that the